The Compressive Strength of Mortar Mixed with Crumb Rubber as Partial Replacement in Fine Aggregate - Muhammad Emir Syamin Muhammad Rizal; Awang Ali Zainul Abidin Awang Ali Rahman; Muhammad Imran Shakir Hussin; Khairi Supar (Multidisciplinary Applied Research and Innovation, 2023)
Rubber crumb may be utilised as a building material, notably as a replacement for fine aggregates, with significant environmental and sustainability benefits. Normal concrete, on the other hand, has limited properties such as low ductility, low impact energy absorption, and low fracture resistance when used in roof tiles. This study focus on the new mixed mortar with rubber crumbs as partial replacement of fine aggregate and to determine the compressive strength and water absorption. This research concentrate on the new mixed roof tiles, which then be compared to a control sample. The research was done by comparing average control sample water absorption percentage and compressive strength with mortar mixed with crumb rubber 5%, 10% and 15% for 7 days and 28 days each sample. This research also includes water absorption testing and compressive strength testing to identify the percentage of water absorption and compressive strength for the fresh mixed concrete. As a consequence, the new mixed roof tiles are projected to maintaining compressive strength and decrease water absorption percentage at optimum limit which is 10%. Rubber crumbs also provide less water absorption since the substance utilised has a lower proportion of water absorption. Finally, waste rubber disposal is a severe environmental problem all over the world due to health concerns and difficulties in land filling. By recycling rubber and using it as a partial fine replacement in mortar, we can create a new improved mortar with a higher water absorption and compressive strength percentage.